Preliminary assessments of debris flow hazard in relation to geological environment changes in mountainous regions, North Vietnam - Tu*, Tran Van; Duc, Dao Minh; Tung, Nguyen Manh; Cong, Van Duy (Vietnam Journal of Earth Sciences, 2016)
Debris flow, widely viewed by geo-scientists as a special combination of landslide and flash flood, causes devastating damages to people and environment in northern mountainous regions of Vietnam. Field observations in the areas damaged by debris flows in northern Vietnam identified types of soils and rocks that were more likely to cause debris flows. Unlike flash floods, almost debris flows occurred at the end of the rainy season when soils and rocks were water-oversaturated thus mechanically weak; this is when pore water pressure decreases, lowering the strength from the soil. Landslides causing debris flows are commonly current slides. The tip of a landslide is often confined within a stream that has a permanent or seasonal flow. Debris flows mainly occur in proluvium, colluvial deposits or tectonic breccia zones. However, not a debris flow initiated in a tectonic breccia zone has been recorded in the northern mountainous regions of Vietnam. Colluvial deposits have been intensively investigated by many researchers worldwide. These deposits are commonly formed in neo-tectonic active zones, weak bed rocks, particularly old metamorphic rocks such as sericite shale, terrigenous and Cenozoic or late Mesozoic volcanic sedimentary rocks that are distributed at steep slopes and/or highly differentiated reliefs. These features appear to be a prerequisite for the exogenous processes, including rolling stones, falling rocks, landslides and surface erosions to occur. To study the mechanical and physical properties of colluvial deposits, the most practical approach is conducting experiments with large-sized samples or on-site experiments. However, this approach is expensive and not always favorable. Applying the rock mechanical theory, it is possible to examine C, j values if values of geological characteristics of rock blocks are known. Thus, the present study attempts clarify the cause-feedback relationship between the change of geological environment and geological hazard in general, and debris flows, in particular, providing a basic scientific insight for studying and predicting debris flows. References Bauziene L., 2000. Colluvisols as a component of erosional and accumulative soil cover structures of east lithuania. European soil Bureau - research report (7), 147-151. Hoek E., Marinos P., 2007. A brief history of the development of the Hoek-Brown failure criterion, Soils and Rocks, 2, 1-8. Irfan T.Y., Tang K.Y., 1992. Effect of the coarse fractions on the shear strength of colluvium. Geo report No 23, Geotechnical Engineering office, Civil Engineering Department Hong Kong. Lai K. W., 2011. Geotechnical properties of colluvial and alluvial deposits in Hong Kong. The 5th cross-strait Conf on Structural and geotechnical engineering (SGE-5), 735-744, Hong Kong China, 13-15 July 2011. Ngo Van Liem, Phan Trong Trinh, Hoang Quang Vinh, Nguyen Van Huong, Nguyen Cong Quan, Tran Van Phong, Nguyen Phuc Dat, 2016. Analyze the correlation between the geomorphic indices and recent tectonics of the Lo River fault zone in southwest of Tam Dao range, Vietnam J. Earth Sci., 38(1), 1-13. Richard E. Gray, 2008. Landslide problems on appalachian colluvial slopes. Geohazards in transportation in the appalachian region, Charleston, WV. Robert W. Fleming, Johnson M. Arvid, 1994. Landslide in Colluvium. U.S. Geological Survey Bulletin 2059-B. Tran Trong Hue (edit), 2004. Integrated assessment of geological disasters in Vietnam territory and prevention solutions (Phase II: The northern mountainous provinces), Report on Phase II of the Independent National project. Institute of Geology, Hanoi, 2003. Tran Van Tu (edit), 1999. Study of the scientific basis of formation and development of mountain floods (including flash floods), proposing the solution of warning, mitigation, and reduction of natural disasters and damage. Report of the project of the Vietnam Centre for Science and Technology, 1998 - 1999. Tran Van Tu, 2012. Scientific basis and method to set up the map of zonation area for sweeping flood, Journal of Sciences of the Earth, 34(3), 7-13.